Developing the marketing experience to increase shopping time: The moderating effect of visit frequency - Silvia Cachero-Martínez; Rodolfo Vázquez-Casielles (Administrative Sciences, 2018)
In the retail sector, the creation of shopping experiences becomes increasingly important to obtain a competitive advantage, and to meet consumers' needs and desires. Knowing how to design and apply these experiences can stimulate consumer engagement and their intention to spend more time at the retailer. Under this premise, the objective of this research is to analyze the relationship between different shopping experience dimensions, consumers' engagement, and their willingness to spend more time at the retailer. Using survey methodology on a sample of 527 consumers, the results show that shopping experiences stimulate the consumers' engagement and their predisposition to spending more time at the store. In addition, a moderating effect of visit frequency to the retailer is observed, such that the higher this is, the more intense the relationship between experience dimensions and consumer engagement will be.
Keywords: 350; shopping experience; retail; consumer engagement; shopping time; shopping frequency